2008
DOI: 10.1021/ef800615e
|View full text |Cite
|
Sign up to set email alerts
|

Role of Naphthenic Acids in Emulsion Tightness for a Low-Total-Acid-Number (TAN)/High-Asphaltenes Oil

Abstract: The emulsion stabilizing properties of a low-total-acid-number (TAN) crude oil, which had initially been attributed to asphaltenes and calcite precipitation, were re-analyzed with regard to the role of organic acids. Despite high asphaltenes content, this crude oil exhibits features classically observed with acidic oils, such as the increase in emulsion stability upon pressure decrease/pH increase or the poor efficiency of demulsifiers. The potential for a significant role of organic acids was confirmed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 27 publications
(56 reference statements)
7
73
0
Order By: Relevance
“…The importance of oxygenated polar compounds as interfacial active components in crude oil is widely acknowledged as one of the primary causes of emulsion stability in crude oil mixtures (Acevedo et al, 1999; Pauchard et al, 2008). Oxygenated polar compounds also play an important role in wettability alteration.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of oxygenated polar compounds as interfacial active components in crude oil is widely acknowledged as one of the primary causes of emulsion stability in crude oil mixtures (Acevedo et al, 1999; Pauchard et al, 2008). Oxygenated polar compounds also play an important role in wettability alteration.…”
Section: Resultsmentioning
confidence: 99%
“…Serang field sludge was reported to be composed of 70% paraffins and iso-paraffins (C 14 -C 28 ), 20% (C 28 -C 30 ) carboxylate salts and < 5% inorganic material (Gallup et al 2002). Large carboxylic acids with molecular weight up to 700 g/mol have been reported (Pauchard et al 2009). Serious challenges arise in the field from sludge formation because of reduced storage capacity, restricted flow of petroleum due to constrictions arising from solid loading in subsea lines, risers and in separation vessels especially after treatment, and poor oil/water separation (Turner and Smith 2005).…”
Section: Sodium Carboxylate Soap Emulsionmentioning
confidence: 99%
“…A study by Pauchard et al (2009) identified asphaltene-naphthenic acid interactions modulated by pH and acid structure as the main factor responsible for changes in interfacial behaviour of naphthenic acids and emulsion stability of a low-TAN crude oil. Asphaltenes are inhibitive to CaN formation.…”
Section: Effect Of Asphaltenes On Calcium Naphthenate Formationmentioning
confidence: 99%
“…Different authors have discussed the surface-active character of oils to combined effects of the presence of carboxylic acids and asphaltenes in crude oils. Accordingly, these carboxylic acids and the asphaltenes perform a synergic effect, resulting in emulsion stabilization [19,42]. Thus, one possibility is that the aggregates formed between these species are the emulsion stabilizing materials.…”
Section: (-) Esi Analysismentioning
confidence: 99%